2021
DOI: 10.1007/s11104-021-04914-z
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐dose placement of phosphorus induces deep rooting of upland rice

Abstract: Upland rice production is often constrained by phosphorus deficiency (P) and drought events. Methods are needed to maximize P use efficiency, while promoting deep root development to mitigate drought. This study evaluates micro-dose P placement as a technique to enhance drought resilience of upland rice, thereby hypothesizing that P placement enhances deep root development, stimulated by the local P supply in the planting hole, compared to broadcast P. MethodsTwo pot experiments were conducted using P deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…Comparison between SRD, micro-dose and full dose P application It was evident from the outcome that the MDP or SRD, both of which have a principle of localized P placement, outperformed the FD broadcast approach almost across all parameters. Localized placement of P promotes root proliferation, expanding the root absorption surface area and capturing more soil nutrients, as supported by previous studies (De Bauw et al, 2021;Jing et al, 2010). This can explain the increase in dry biomass production and P uptake in our nding (Table 2), as root proliferation in nutrient-rich areas can compensate for uneven nutrient distribution across the root system (Robinson, 2001).…”
Section: Effect Of Srd On Chilli (Capsicum Annuum) In Different P Con...supporting
confidence: 87%
“…Comparison between SRD, micro-dose and full dose P application It was evident from the outcome that the MDP or SRD, both of which have a principle of localized P placement, outperformed the FD broadcast approach almost across all parameters. Localized placement of P promotes root proliferation, expanding the root absorption surface area and capturing more soil nutrients, as supported by previous studies (De Bauw et al, 2021;Jing et al, 2010). This can explain the increase in dry biomass production and P uptake in our nding (Table 2), as root proliferation in nutrient-rich areas can compensate for uneven nutrient distribution across the root system (Robinson, 2001).…”
Section: Effect Of Srd On Chilli (Capsicum Annuum) In Different P Con...supporting
confidence: 87%
“…Phosphorus is usually heterogeneously distributed in natural and agroecological systems (Adediran et al, 2020;George et al, 2018;Wang et al, 2020). To access patchy P effectively, plants have evolved diverse below-ground strategies which include increasing photosynthesis partitioning to grow roots, stimulating ne-root proliferation, and enhancing exudation of P-mobilizing compounds in nutrient-rich zone (De Bauw et al, 2021;Hodge, 2004;Jing et al, 2010). For instance, crops could invest large ratio of photosynthesis into nutrient-rich zone, produce long roots with diameter lower than 0.5 mm, and increase the secretion of acid phosphatase (Gao et al, 2019;Jing et al, 2012Jing et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Trifolium subterraneum L. Losa proliferated long roots in the top soil containing abundant plant-available P compared with the genotype Napier (McLachlan et al, 2020a). Besides, the effect size of heterogeneous nutrient on root proliferation and crop yield productivity depends on levels of P fertilization (De Bauw et al, 2021;Ma et al, 2020). Previous studies have demonstrated that heterogeneous P supply stimulated root allocation in the P-rich soil volume, and elicited large P content in crops fertilizing with low-dose P compared with high-dose P application (Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus is usually heterogeneously distributed in natural and agroecological systems (George et al, 2018;Adediran et al, 2020;Wang et al, 2020). To access patchy P effectively, plants have evolved diverse belowground strategies, which include increasing photosynthesis partitioning to grow roots, stimulating local ne-root growth, and enhancing exudation of P-mobilizing compounds in nutrient-rich zones (Hodge, 2004;Jing et al, 2010;De Bauw et al, 2021). For instance, crops could invest a large ratio of photosynthesis into nutrient-rich zones, produce long and ne roots, and increase the secretion of acid phosphatase (Jing et al, 2012(Jing et al, , 2022Gao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Trifolium subterraneum L. Losa developed long roots in the topsoil containing abundant plant available P compared with the genotype Napier (McLachlan et al, 2020a). In addition, the effect size of localized nutrients on root growth and crop yield productivity depends on the levels of P fertilization (Ma et al, 2020;De Bauw et al, 2021). Previous studies have demonstrated that localized P supply stimulated root allocation in P-rich soil and elicited a large P uptake in crops fertilized with lowdose P compared with high-dose P application (Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%